2022
DOI: 10.3390/w14213432
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Cadmium and Lead Contamination: Sources, Fate, Mechanism, Health Effects and Remediation Methods

Abstract: Cadmium and lead soil contamination is a widespread environmental problem that requires profound and sustainable solutions. These toxic elements can be naturally occurring on the Earth’s crust or from man-made origins. Cadmium and lead could accumulate and translocate in soil over the long term. Thus, their risk of entering the food chain is extremely elevated and their effects on the living organisms in the food web are of great concern. The main purpose of this review study is to emphasize the risk to human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 118 publications
0
14
0
Order By: Relevance
“…Most of the cadmium accumulated by humans comes from agricultural activities (use of phosphate fertilizers rich in cadmium, spreading of waste sludge in market gardening areas) but also from industrial activities (zinc and lead metallurgy, etc.) [47]. Indeed, most of the vegetables used come from market gardening.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the cadmium accumulated by humans comes from agricultural activities (use of phosphate fertilizers rich in cadmium, spreading of waste sludge in market gardening areas) but also from industrial activities (zinc and lead metallurgy, etc.) [47]. Indeed, most of the vegetables used come from market gardening.…”
Section: Discussionmentioning
confidence: 99%
“…Atmospheric deposition of metals from metal smelting and fossil fuel incineration, as well as leachates from waste dumps and mines, poses threats to both terrestrial and aquatic environments (Hovmand et al, 2008; Xing et al, 2020). Average concentrations of cadmium in soil globally are around 0.36 mg/kg (Kubier et al, 2019) but occur in higher concentrations in areas impacted by related industries with concentrations as high as 171.72 mg/kg (Bouida et al, 2022). A study examining surface waters surrounding industrial areas found up to 0.74 mg/L of cadmium in samples obtained adjacent to a coal‐fired power station (Nalawade et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Anthropogenic activities can produce heavy metals which can be environmental pollutants [ 1 ]. In addition, the general public may be exposed to naturally occurring heavy metals even if they are not occupationally exposed to heavy metals [ 2 ]. Heavy metals enter the body through means of air, water, and food and are absorbed [ 3 ].…”
Section: Introductionmentioning
confidence: 99%